Heterogeneous demand for agricultural lime in Tanzania: Recent empirical evidence and implications for policy - Gebrekidan, Bisrat; Jaleta, Moti; Chamberlin, Jordan; Kuboja, Nicholaus M. (CGIAR System Organization, 2025)
Soil acidity and related agricultural productivity constraints have re-emerged as a policy priority in several countries in Sub-Saharan Africa in recent years. However, despite well-documented agronomic benefits, the use of agricultural lime to address soil acidity remains limited by farmers, and value-chains for agricultural lime remain poorly developed in most acidic areas. As countries with acidity constraints evaluate their policy options– which may include targeted extension, investments in lime production and market development, or inclusion of lime in input subsidy schemes– they are constrained by limited evidence on how farmers value lime, what drives their demand, and how demand would respond to pricing changes in local markets. To address this gap in one country with significant soil acidity constraints, Tanzania, we estimate the willingness of smallholder farmers to pay for lime using a double bounded dichotomous choice contingent valuation method. Our analysis is based on survey data from 600 randomly selected farm households in Iringa District, Tanzania, an area characterized by high soil acidity, an existing lime supply chain, but limited lime uptake by local farmers. The estimated mean willingness to pay was found to be 4.67 US dollars per 50 kilogram bag of lime, closely aligning with the prevailing market prices. However, the willingness to pay varies considerably among farmers. Social exposure, measured by the number of known lime users, is the strongest predictor of demand, with the willingness to pay significantly higher for farmers who know more than five other users. WTP is higher for farmers with prior lime experience, exposure to training, level of education, landholding size, and livestock ownership, and is negatively correlated with the degree of present bias. Inverse demand curves show that only about half of farmers are willing to pay the current market price. An effective intervention requires simultaneous investments in demand creation, improved access to liquidity, and coordination across the lime supply chain. Our results not only provide useful guidance to policymakers in Tanzania but also to governments and private sector actors in similar settings in the region.